An adaptive coordination control solution to boost frequency stability for a hybrid distributed generation system. - Hossam S Salama; Gaber Magdy; Abualkasim Bakeer; Thamer A H Alghamdi; Mohammed Alenezi; Mahmoud Rihan (PLoS ONE)
Under the current global circumstances, the urgent need to exploit renewable energy sources (RESs) is increasing. Increased penetration of RESs in hybrid distributed generation systems (HDGSs) poses a challenge due to the unsettled nature of RESs on frequency stability (FS). So, coordination between RESs is essential to sustaining FS. To boost FS in HDGSs, this study presents an adaptive coordination control (ACC) solution regarding RESs, a fuel cell (FC)-based energy storage system (ESS), and an aqua electrolyzer (AE) for producing hydrogen. In the studied system, the surplus energy of RESs is employed to supply electrolysis by AE to store hydrogen energy inside FC. The proposed ACC solution employs fuzzy control to dynamically adjust the RES energy ratio allocated to AE (the surplus energy "Kn" is a fraction of the overall RES-generated energy). The studied HDGS includes photovoltaic (PV) plants, wind turbines (WT), AE coupled with FCs, ESSs (e.g., flywheels and batteries), and diesel generators (DG). The suggested solution changes Kn according to the frequency deviations to maximize the benefits of RESs alongside damping frequency variations. This study examined the proposed solution under different loading situations and compared it to previous research that took Kn as a fixed value.